Social support network and received support at stressful events - Hlebec, Valentina (Metodološki zvezki, 2009)
Many studies in the field of social support (e.g., Hobfoll, 1985; Thoits, 1985; Cutrona and Russell, 1990; Kienan, 1997) show that the effectiveness of a certain type of provided support and mechanisms by which the support works are often highly dependent on a specific situation, where support is needed. For instance, emotional support may be provided in a situation (e.g., an accident), where an affected person needs or expects help of a more practical kind. The provided unsuitable type of support may thus cause additional stress, dissatisfaction, feelings of being misunderstood, controlled or alienated. The context of a specific situation therefore conditions how effective a certain type of support can be. When selecting a measurement instrument presumed to be the best for assessing social support networks and social support functions we have to consider whether to ask a lot of questions about the social support network, the received social support and the perception of social support using complex items, such as name generators, or whether there are simpler ways at our disposal to correctly assess the social support provision, such as role relationship items. We should also decide whether to measure only the perception of social support or the actually received support at particular occasions as well. In this paper we compare and analyze the composition of the social support network assessed by the Antonucci's hierarchical approach, the perceived social support within social support network, and the role relation approach based on received support during 15 major life changes as they have occurred within the last three years. The composition of the social support network (overall and partial across four types of social support) is compared to the overall composition of received support.
Keywords: Social support; Socialna opora; Družbena omrežja; Social networks; Analiza omrežij; Network analysis; stres